Manajemen risiko finansial di perbankan syariah Indonesia: Kajian literatur atas ciri-ciri pembiayaan bermasalah dan strategi penyelesaiannya - Huda, Muhammad Alamul (Maliki Interdisciplinary Journal, 2024)
The purpose of this article is to find out the characteristics of problematic financing and find out resolution strategies at Sharia Banks in Indonesia. This research comes from a literature review. In the case of financing problems, Islamic banks try to prevent and rescue them so that they do not cause losses and other related risks. Several rescue actions were taken, such as providing financing restructuring. If rescue is not possible then the steps taken are arbitration or through related legal bodies.